Livin' on a prayer : carving spaces of faith in Singapore - Pillai, H Sharanya (2017)
Singapore is home to 10 official religions, and the country’s religious pluralism is visible in unique ways. During the annual Formula One Grand Prix, for instance, it is a tradition for a group of 10 religious leaders of different faiths to gather at the race track and pray for the safety of the event. The 350m-long Telok Ayer Street also hosts a temple, mosque and church – all a stone’s throw from each other. According to a study by the Pew Research Center in 2014, Singapore is the most religiously diverse country in the world. Singapore’s secularism policy and strict laws preventing actions that could cause divisions on the grounds of religion have nurtured a safe atmosphere for diverse religious communities to thrive. The freedom of worship is enshrined in the constitution, and Prime Minister Lee Hsien Loong has described the religious harmony as “a very unnatural state of affairs”. In this feature writing project, we seek to capture how minority and non-mainstream religious communities have managed to jostle for place and co-exist. For instance, religions that would otherwise be persecuted elsewhere, such as the Baha’i faith, have found a safe haven here. A growing community of migrant workers have retained their cultural practices and built their own places of worship. Support groups have also sprung up for those trying to reconcile their religion with their sexual orientation as lesbian, gay, bisexual or transgender. The Jehovah’s Witnesses, more than 45 years after their activities were officially deregistered, continue to quietly thrive from beneath the shadows. Amid this diversity, though, is a growing trend of non-religiosity among the young. The marketplace of religious ideas means Singaporeans now move more quickly from one faith to another, surf their options and search for a better fit, but many end up shedding their religious identity and leaving the religious traditions in which they grew up in.